A Study of The Effect of Insulin Resistance on Cardiovascular Health in Diabetes Patients - Sunil K. Sahu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Insulin resistance in type 2 diabetes mellitus (T2DM) affects cardiovascular health. This study examines how varying levels of insulin resistance impact cardiovascular control during exercise. To determine the effect of insulin resistance on cardiovascular metrics such as heart rate, blood pressure, and exercise capacity in T2DM patients. Secondary data from NHANES and ClinicalTrials.gov were analysed. Participants (n=500) with T2DM were categorized by insulin resistance levels (low, moderate, high). Cardiovascular metrics during exercise were assessed using statistical analyses. Higher insulin resistance was associated with higher resting heart rates, reduced heart rate recovery, increased blood pressure, and lower VO2 max. Insulin resistance significantly predicted impaired cardiovascular control during exercise. Elevated insulin resistance correlates with worsened cardiovascular responses to exercise in T2DM patients. These findings highlight the need for personalized exercise strategies in diabetes management.